SINTESIS DAN KARAKTERISASI SELULOSA BAKTERI-SITRATKITOSAN SEBAGAI PEMBALUT LUKA ANTIMIKROBA - Farah Nurlidar; Lely Hardiningsih; Darmawan Darwis (Research Center for Chemistry - LIPI, 2013)
Bacterial cellulose, produced by Acetobacter xylinum, is an interesting material for using as a wound dressing since it provides moist environment to a wound resulting in a better wound healing. However, bacterial cellulose (BC) itself has no antibacterial activity to prevent wound infection. To achieve antibacterial activity, chitosan were impregnated into bacterial cellulose by cross linking reaction using citric acid as cross linker. The thickness, water and saline absorption capacity, water vapour transmission rate (WVTR), mechanical properties and antibacterial activity of composite were investigated. The result show an important increase in absorption capacity when BC was treated with citric acid and chitosan and the maximum value was reached at 21.5 gig in DM water and 8.2 gig in salinesolution. The WVTR analysis of all the test membranes was found to be less than WVTR value of control without sample. The result also showed that bacterial cellulose-citrate-chitosan (BC-AST) exhibited antibacterial activity against E. coli, S. typhi, P. aeruginosa and S. aureusKeywords: Antibacterial, bacterial cellulose, citric acid, chitosan, wounddressing.